Plasma thyrocalcitonin and parathyroid hormone concentrations in early neonatal hypocalcaemia. Issue 6 (June 1987) - Romagnoli, C; Zecca, E; Tortorolo, G; Diodato, A; Fazzini, G; Sorcini-Carta, M
Abstract : During the first week of life serum calcium, phosphorus, magnesium, immunoreactive thyrocalcitonin hormone, and parathyroid hormone concentrations were determined daily in 36 preterm and 29 small for gestational age, full term, healthy infants. Preterm babies with early neonatal hypocalcaemia had significantly higher concentrations of serum thyrocalcitonin hormone in the first four days of life than normocalcaemic preterm babies. Parathyroid hormone concentrations were similar in hypocalcaemic and normocalcaemic infants. In contrast, in the full term group no significant differences were detected in thyrocalcitonin hormone and parathyroid hormone patterns between hypocalcaemic and normocalcaemic subjects. This suggests two different pathogeneses for early hypocalcaemia in low birthweight infants. Hyperthyrocalcitoninaemia seems to be the main determining factor in preterm infants, while a non-hormonal pathogenesis should be considered in full term infants who are small for gestational age.